Cytological investigations of the effect of colchicine on meiosis in Lilium hybrid cv. Black Beauty microsporocytes - Toledo, L. A. [UNESP]; Bennett, M. D.; Stern, H. (Springer Nature, 1979)
Using colchicine, two methods have been successfully applied for the induction of tetraploid meiocytes at premeiotic mitosis in the near achiasmate diploid hybrid cultivar Black Beauty of Lilium. The experiments were aimed at understanding whether the achiasmate condition is attributable to insufficient homology for effective pairing or to some genie defect in order to interpret the data obtained from molecular studies. Cytological observations demonstrate a strong correlation between the induction of tetraploidy and subsequent chiasma formation. The chiasma frequency per cell in untreated diploid control meiocytes ranged from 0 to 8 (mean 2.25), while in colchicine treated undoubled cells sampled 14±2 days after the start of treatment it ranged from 0 to 2 (mean 0.148). By comparison, the chiasma frequency per cell in colchicine-doubled tetraploid cells ranged from 29 to 51 (mean 42.24), such cells showing complete or near complete bivalent pairing. These results, similar to those reported previously for other higher plant species, demonstrate that the achiasmatic condition in Black Beauty is not due to a genie defect. The methods developed have made possible hitherto inaccessible biochemical analyses of meiocytes that had been treated with colchicine or other chemicals at premeiotic stages. © 1979 Springer-Verlag.